1969
DOI: 10.1128/jb.99.2.535-543.1969
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Mapping: Functional Organization of the Ribosomal and Transfer Ribonucleic Acid Cistrons in the Bacillus subtilis Genome

Abstract: The transcriptional mapping method developed previously has been used to investigate the functional organization of the ribosomal ribonucleic acid (rRNA) and transfer ribonucleic acid (tRNA) cistrons in the Bacillus subtilis genome. The sensitivities of the syntheses of these RNA species to actinomycin D indicated that (i) large polycistronic groupings of the tRNA cistrons exist, but (ii) the 16S and 23S rRNA cistrons are probably transcribed as individual units, and (iii) each 5S rRNA cistron is part of an op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

1970
1970
1985
1985

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(9 citation statements)
references
References 14 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…Spacer tRNA genes are found in only a few rRNA gene sets. Of the 10 rRNA gene sets known to occur in B. subtilis, 2 have been shown to have spacer tRNA genes between the 16S and 23S rRNA genes. In both cases, these sequences code for isoleucine and alanine tRNAs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Spacer tRNA genes are found in only a few rRNA gene sets. Of the 10 rRNA gene sets known to occur in B. subtilis, 2 have been shown to have spacer tRNA genes between the 16S and 23S rRNA genes. In both cases, these sequences code for isoleucine and alanine tRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…Mapping of tRNA and rRNA Gene Clusters One unusual aspect of tRNA gene organization in B. subtilis was already recognized in the 1960s: the tRNA genes are highly clustered. Transcriptional mapping studies to elucidate the functional organization of ribosomal ribonucleic acid (rRNA) and tRNA genes in B. subtilis indicated that tRNA genes would be clustered in groups in large transcriptional units (2). Density transfer experiments also suggested that the majority of both tRNA and rRNA genes were located in two regions of the chromosome, one near the origin of replication and a second near the terminus (38,47).…”
Section: Organization Of Trna Gene Regionsmentioning
confidence: 99%
“…Differential effect of Act D on RNA synthesis. There is now evidence which suggests that Act D inhibits the transcription of large RNA species to a greater extent than that of smaller RNA species (4,32). This effect was explained on the basis of a differential probability of Act D molecules binding to any given cistron.…”
mentioning
confidence: 99%
“…There have been a number of reports that Act D selectively inhibits the larger RNA species to a greater extent than smaller RNA species (4,32). Perry and Kelley (32) have calculated that not all the Act D bound to DNA effectively inhibited RNA synthesis and that probably only 1 Act D per 101 nucleotides was effective.…”
mentioning
confidence: 99%
“…In B. subtilis, tRNAs are encoded in multiple polycistronic operons with ribosomal proteins [84]. The mRNA is then processed into the final tRNAs.…”
Section: Regulation Of Trna Levels and Trna Charging In Biofilmmentioning
confidence: 99%